A Rare Cause of Neck Mass: Pilomatrixoma - Caner Turan; Ali Yurtseven; Eylem Ulaş Saz (Galenos Yayinevi, 2018)
Pilomatrixoma (pilomatricoma) (Malherbe's calcifying epithelioma), although rare, is the second most frequent benign skin tumour in childhood. It originates from the hair follicles. It is most commonly seen on the head and in the neck region, it also may be located on the upper extremities. Diagnosis may be confused with other skin tumours and malignancies. In this case, we report on a patient who presented with a mass on the neck diagnosed as a pilomatrixoma.